1995
DOI: 10.1111/j.1432-1033.1995.0480n.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a cAMP-Binding Protein of Volvox carteri f. nagariensis Iyengar

Abstract: Two cAMP‐binding proteins, cbpl and cbp2, were purified from the cytoplasm of the green alga Volvox carteri. Both proteins have a native molecular mass of 90 kDa as determined by gel filtration. cbp2 was purified to apparent electrophoretic homogeneity, having a subunit molecular mass of 42 kDa as determined by SDS/PAGE. The cbp1 preparation contains a 42‐kDa and a 44‐kDa band. The cAMP‐binding activity is not associated with protein kinase activity. Tryptic peptides of cbp2 were sequenced by automated Edman d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, it was reported that signal transduction with cAMP as a second messenger is mediated in Volvox by intracellular cAMP receptors called cAMPbinding proteins (Feldwisch et al 1995). Furthermore, disintegration of sperm packets of sexual male Volvox algae has been observed after the addition of dibutyryl-cAMP (Waffenschmidt et al 1990).…”
Section: Histidine Kinase Rhodopsinsmentioning
confidence: 98%
“…Moreover, it was reported that signal transduction with cAMP as a second messenger is mediated in Volvox by intracellular cAMP receptors called cAMPbinding proteins (Feldwisch et al 1995). Furthermore, disintegration of sperm packets of sexual male Volvox algae has been observed after the addition of dibutyryl-cAMP (Waffenschmidt et al 1990).…”
Section: Histidine Kinase Rhodopsinsmentioning
confidence: 98%